2018
DOI: 10.1523/eneuro.0024-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Eye Field Inactivation Reduces Saccade Preparation in the Superior Colliculus but Does Not Alter How Preparatory Activity Relates to Saccades of a Given Latency

Abstract: A neural correlate for saccadic reaction times (SRTs) in the gap saccade task is the level of low-frequency activity in the intermediate layers of the superior colliculus (iSC) just before visual target onset: greater levels of such preparatory iSC low-frequency activity precede shorter SRTs. The frontal eye fields (FEFs) are one likely source of iSC preparatory activity, since FEF preparatory activity is also inversely related to SRT. To better understand the FEF’s role in saccade preparation, and the way in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 68 publications
3
17
0
Order By: Relevance
“…This coordination between pupil size and saccades is also observed in human studies in the tasks involving pro‐ or anti‐saccade generation (Dalmaso et al., 2020; Jainta et al., 2011; Wang et al., 2015, 2016, 2017). Trials with faster SRTs accompany trials with larger pupil dilation responses, arguably through low‐frequency saccade preparatory activity observed in the FEF and SC (Basso & Wurtz, 1998; Dash et al., 2018; Dorris et al., 1997; Everling & Munoz, 2000; Jagadisan & Gandhi, 2017; Krauzlis, 2003). Furthermore, a recent monkey study has showed decreased SC preparatory activity after FEF inactivation (Dash et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This coordination between pupil size and saccades is also observed in human studies in the tasks involving pro‐ or anti‐saccade generation (Dalmaso et al., 2020; Jainta et al., 2011; Wang et al., 2015, 2016, 2017). Trials with faster SRTs accompany trials with larger pupil dilation responses, arguably through low‐frequency saccade preparatory activity observed in the FEF and SC (Basso & Wurtz, 1998; Dash et al., 2018; Dorris et al., 1997; Everling & Munoz, 2000; Jagadisan & Gandhi, 2017; Krauzlis, 2003). Furthermore, a recent monkey study has showed decreased SC preparatory activity after FEF inactivation (Dash et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Trials with faster SRTs accompany trials with larger pupil dilation responses, arguably through low‐frequency saccade preparatory activity observed in the FEF and SC (Basso & Wurtz, 1998; Dash et al., 2018; Dorris et al., 1997; Everling & Munoz, 2000; Jagadisan & Gandhi, 2017; Krauzlis, 2003). Furthermore, a recent monkey study has showed decreased SC preparatory activity after FEF inactivation (Dash et al., 2018). Consistently, here we found correlations between pupil size and SRTs in the contralateral condition in the vertex stimulation, and the diminished correlation with FEF stimulation, suggesting a role of human FEF in mediating this coupling between pupil size and SRTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peel et al (2017) reported activity decrements of the superior colliculus neurons when the frontal-eye-field in monkeys was cryogenically inactivated. More recently, Dash et al (2018) showed that FEF inactivation correlated with reduced occurrence of express saccades relative to control conditions. Critically, these findings indicate that the cortical top-down signals to the superior colliculus can modulate the express visuomotor transformations operated by this midbrain structure.…”
Section: Discussionmentioning
confidence: 99%
“…A causal role of the frontal eye field (FEF) in initiating and overall in generating saccades has been demonstrated in two ways: Electrical microstimulation of this region evokes saccades (Bruce et al, 1985; Opris et al, 2001; Robinson and Fuchs, 1969) and its pharmacological inactivation impairs the generation of saccades (Dash et al, 2018; Sommer and Tehovnik, 1997). To explain how single neurons in this region could contribute to saccade initiation, (Hanes and Schall, 1996) suggested a “variable rate” model.…”
Section: Introductionmentioning
confidence: 99%